Komunikasi Interpersonal pada Pengguna Aplikasi Kencan Online dalam Upaya Menjalin Hubungan - Sahrin, Cahyani Alfi; Rahmatul Iman, Topan (Connected: Jurnal Ilmu Komunikasi, 2023)
Interpersonal communication is the basis for closeness and openness between people. Bumble as an application that provides services to meet new people without having to meet face to face. In this study, researchers wanted to find out how interpersonal communication is with online dating application users in an effort to establish relationships. The research method that researchers use is a qualitative approach method. The research subjects were selected by purposive sampling based on two criteria, so that eight informants were selected. To obtain data, researchers conducted in-depth interviews with eight informants both online and online. This study was analyzed using the theory of social penetration put forward by Irwin Altman and Dalmas Taylor to obtain the result that of the 8 (eight) informants interviewed, there were 8 (eight) informants or all informants went through the orientation stage, then 6 (six) informants reached the exchange stage. active exploration which means that the other 2 (two) informants only reached the previous stage, continued from the six informants, only 3 (three) informants reached the affective stage, and the 3 (three) informants also turned out to be able to reach the last stage in social penetration i.e. stable exchange stage. So that not all users can go through the four stages of getting to know new people or establishing relationships. This can depend on the openness of each individual in going through each phase of social penetration to forge deeper relationships using the Bumble application.